2021
DOI: 10.1002/adma.202007073
|View full text |Cite
|
Sign up to set email alerts
|

Surface Wettability of Nanoparticle Modulated Sonothrombolysis

Abstract: Sonodynamic therapy (SDT) is a non‐invasive and highly penetrating treatment strategy under ultrasound irradiation. However, uncertainty in the mechanism of SDT has seriously hindered its future clinical application. Here, the mechanism of SDT enhanced by the wettability of nanoparticles is investigated. Nanoparticles can adsorb and stabilize nanobubbles in liquid, thus enhancing SDT efficiency. The stability of the nanobubbles is positively correlated with the desorption energy of the nanoparticles, which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 43 publications
0
52
0
Order By: Relevance
“…[62] In vitro experiments revealed that TiO 2 -Ce6-CpG showed an efficient internalization into the cells (Figure 7c). After various experimental analysis, it was found that CD11c and CD86 as the representative markers of DCs maturation were up-regulated, Enhanced SDT and immune response stimulation [62] Mn-MOF Mn-MOF 4T1 Cyclooxygenase activity rise and GSH content drop [88] sPD-1/Ce6-NBs Ce6, NBs HCC Induced UTND, enhanced SDT and immune response [89] RBC-mTNPs@AQ4N mTNPs, AQ4N, RBC MCF-7 Immune escape, hypoxia activation chemotherapy [63] THPP-Oxa(IV)-PEG THPP, Oxa(IV)SA 2 , PEG 5k -COOH CT26 Immunogenic nanodrug and radioisotope imaging [90] PIH-NO HSA-NO, FDC, IR780 4T1 Mitochondrial damage, drug accumulation, and M2 macrophage polarization into M1 phenotypes [91] LiP-PFH DPPC, DSPC, DSPE-PEG2000 4T1 Enhanced anti-tumor immunity [92] OI_NPs OXP, ICG, PFP ID8 Improved optical and ultrasonic imaging [93] FA-MnPs MNP, FA TNBC M2 macrophages polarized to M1 phenotype, ICD response to activate NK, DC maturation [94] RSL3@O 2 -ICG NBS NBS, ICG, RSL3 HCC Ferroptosis [87] SnNSs@PEG 2D SnNS, PEG H1299 Excellent photothermal efficiency [64] MPN-PALF LOX, ATO, Ce6 4T1 Relieving acidic TME [95] MG@PNPs PMnC, Gox 4T1 MR/PA dual-mode imaging and tumor starvation treatment [96] 𝛼-Fe 2 O 3 @Pt 𝛼-Fe 2 O 3 , Pt 4T1 Inhibiting electron-hole pairs recombination for ROS production [97] P/M@CasMTH1 MOF, CRISPR-Cas9, MTH1 A549 Controlled release and enhanced SDT [86] MitoCAT-g CAT-g, CA, TPP HCC GSH exhaustion [84] Wettability of nanoparticles MSN, PSS Thrombus Enhanced SDT [59] FA-N-GQds FA, N-GQD, pyridine N, pyrrole N MDA-MB-231 High tumor labeling rate [61] ZIF-8 NCS ZIF-8, MOF 4T1 Acidic TME modulation [80] IRO@FANP PLGA, PEG, FA ID8 Enhanced SDT [98] IR820@NCP IR820, FTS HCC Tumor aggregation and fluorescence imaging [99] Pd/H-TiO 2 NSS Pd, NSS C6 Enhanced CDT and SDT [100] indicating that nanosonosensitizer TiO 2 -Ce6-CpG could significantly promote DCs maturation in vitro. In the in vivo experiment of female C57BL/6 mice inoculated with Hepa1-6, it was found that the treatment with such composite sonosensitizers (TiO 2 -Ce6-CpG) combination with PD-L1 inhibitor could not only effectively inhibit the primary tumor but also significantly delay the growth of distant tumors (Figure…”
Section: Nanobiotechnology-augmented Sdt In Combination With Immunoth...mentioning
confidence: 99%
See 2 more Smart Citations
“…[62] In vitro experiments revealed that TiO 2 -Ce6-CpG showed an efficient internalization into the cells (Figure 7c). After various experimental analysis, it was found that CD11c and CD86 as the representative markers of DCs maturation were up-regulated, Enhanced SDT and immune response stimulation [62] Mn-MOF Mn-MOF 4T1 Cyclooxygenase activity rise and GSH content drop [88] sPD-1/Ce6-NBs Ce6, NBs HCC Induced UTND, enhanced SDT and immune response [89] RBC-mTNPs@AQ4N mTNPs, AQ4N, RBC MCF-7 Immune escape, hypoxia activation chemotherapy [63] THPP-Oxa(IV)-PEG THPP, Oxa(IV)SA 2 , PEG 5k -COOH CT26 Immunogenic nanodrug and radioisotope imaging [90] PIH-NO HSA-NO, FDC, IR780 4T1 Mitochondrial damage, drug accumulation, and M2 macrophage polarization into M1 phenotypes [91] LiP-PFH DPPC, DSPC, DSPE-PEG2000 4T1 Enhanced anti-tumor immunity [92] OI_NPs OXP, ICG, PFP ID8 Improved optical and ultrasonic imaging [93] FA-MnPs MNP, FA TNBC M2 macrophages polarized to M1 phenotype, ICD response to activate NK, DC maturation [94] RSL3@O 2 -ICG NBS NBS, ICG, RSL3 HCC Ferroptosis [87] SnNSs@PEG 2D SnNS, PEG H1299 Excellent photothermal efficiency [64] MPN-PALF LOX, ATO, Ce6 4T1 Relieving acidic TME [95] MG@PNPs PMnC, Gox 4T1 MR/PA dual-mode imaging and tumor starvation treatment [96] 𝛼-Fe 2 O 3 @Pt 𝛼-Fe 2 O 3 , Pt 4T1 Inhibiting electron-hole pairs recombination for ROS production [97] P/M@CasMTH1 MOF, CRISPR-Cas9, MTH1 A549 Controlled release and enhanced SDT [86] MitoCAT-g CAT-g, CA, TPP HCC GSH exhaustion [84] Wettability of nanoparticles MSN, PSS Thrombus Enhanced SDT [59] FA-N-GQds FA, N-GQD, pyridine N, pyrrole N MDA-MB-231 High tumor labeling rate [61] ZIF-8 NCS ZIF-8, MOF 4T1 Acidic TME modulation [80] IRO@FANP PLGA, PEG, FA ID8 Enhanced SDT [98] IR820@NCP IR820, FTS HCC Tumor aggregation and fluorescence imaging [99] Pd/H-TiO 2 NSS Pd, NSS C6 Enhanced CDT and SDT [100] indicating that nanosonosensitizer TiO 2 -Ce6-CpG could significantly promote DCs maturation in vitro. In the in vivo experiment of female C57BL/6 mice inoculated with Hepa1-6, it was found that the treatment with such composite sonosensitizers (TiO 2 -Ce6-CpG) combination with PD-L1 inhibitor could not only effectively inhibit the primary tumor but also significantly delay the growth of distant tumors (Figure…”
Section: Nanobiotechnology-augmented Sdt In Combination With Immunoth...mentioning
confidence: 99%
“…[ 28 , 55 ] Generally, cavitation is classified into inertial cavitation and stable cavitation. [ 55 , 58 ] As cavitation proceeds, energy is released to give birth to shock waves, microjets, high temperature, high pressure, and so on, [ 59 , 60 ] and these biophysical effects could be used enhance HIFU temperature and sonocatalytic ROS production for killing tumor cells.…”
Section: Clinical Physiotherapy‐activated or Combined Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Red cell was extracted from fresh rat whole blood and mixed with PBS to prepare 2% red blood cell suspension, then incubated with PBS, 0.1%Triton-100, and GPRPP-Y8U@P solution at different concentrations for 3 hours to con rm the blood compatibility [53] . Finally, the absorbance of the supernatant was determined at 540 nm using a microplate reader, re ecting the hemoglobin from lysed red blood cells.…”
Section: Hemolysis Assaymentioning
confidence: 99%
“…Finally, the absorbance of the supernatant was determined at 540 nm using a microplate reader, re ecting the hemoglobin from lysed red blood cells. PBS and 0.1%Triton-100 were used as a negative and positive group, respectively [53] .…”
Section: Hemolysis Assaymentioning
confidence: 99%